2012
DOI: 10.4097/kjae.2012.62.2.184
|View full text |Cite
|
Sign up to set email alerts
|

Airway fire injury during rigid bronchoscopy in a patient with a silicon stent -A case report-

Abstract: Therapeutic bronchoscopy is widely employed as an effective first-line treatment for patients with central airway obstructions. Airway fires during rigid bronchoscopy are rare, but can have potentially devastating consequences. Pulmonologist and anesthesiologist undertaking this type of procedure should be aware of this serious problem and be familiar with measures to avoid this possibly fatal complication. We report the case of a 24-year-old patient with a silicone stent who experienced an electrocautery-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Various medical devices can be implicated in this complication. Several reports in the medical literature described thermal injuries associated with anesthetic care [ 11 , 12 ]. Thermal injuries during minimally invasive surgeries have been reported in the settings of abdominal laparoscopic surgery and gastrointestinal endoscopy [ 9 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various medical devices can be implicated in this complication. Several reports in the medical literature described thermal injuries associated with anesthetic care [ 11 , 12 ]. Thermal injuries during minimally invasive surgeries have been reported in the settings of abdominal laparoscopic surgery and gastrointestinal endoscopy [ 9 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al reported a case of airway fire involving a silicon stent used for dilatation of tracheal stenosis. 7 According to ECRI, an oxygen-enriched environment is a contributing factor in 74% of surgical fires. 4 Barker and Polson demonstrated that while a plastic face mask melts when exposed to an open flame, it will ignite into flames when as little as 3 l/min of oxygen is flowing through it.…”
Section: Discussionmentioning
confidence: 99%
“…An underestimated complication is ''airway fire'' related to laser procedures during advanced bronchoscopy. Analogous to some Ear-nose & throat (ENT) surgeries, such incidents have been reported in patients undergoing advanced pulmonary procedures [57]. Silicone stents used during some advanced procedures pose a particular risk as they supply fuel to the fire [58].…”
Section: Complicationsmentioning
confidence: 99%